Bibliography: Manuel González Prada: Positivism, Anarchism And Literary Criticism - Podestá, Bruno (1974)
This bibliography is a derived product of the research “Political Ideology and Labor Movements” (first phase: anarchism in Peru), in process at the Center Of Research of University of Pacífico. The figure and work of Manuel González Prada (1848-1918) in the context of the previous research is of vital importance. For that reason we offer this little work, with the intention to collaborate with future research about the subject. This bibliography tries to cover, in the most exhaustive manner possible; the publications appeared in English and Spanish until April 1972.